Rekonstruksi Desain Kontrak Akad Musyarakah Pada Lembaga Keuangan Syariah Melalui Pendekatan Hukum Dan Ekonomi - Mira Mira; Nurfadilla K; Rismawati Rismawati; Muh Nuran Raja Al-fathah; Kamaruddin Arsyad (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the optimization of musyarakah contract design in Islamic financial institutions from both legal and economic perspectives. Employing a descriptive qualitative approach, the research explores normative and conceptual aspects of musyarakah contracts through library research methods. Data were collected from various secondary sources such as Islamic law and economics textbooks, academic journals, fatwas issued by the National Sharia Council (DSN-MUI), regulations from the Financial Services Authority (OJK), and reports from Islamic financial institutions. The data analysis was conducted thematically by classifying information based on key themes including contract legality, principles of sharia justice, contract flexibility, risk management, and innovation in musyarakah practices. Data validity was ensured through literature source triangulation to confirm and compare related scientific documents and regulations, thereby producing objective and academically accountable conclusions. The findings of this study are expected to contribute to the development of musyarakah contracts that align with Islamic legal principles and support the sustainability of the sharia economic system